2021
DOI: 10.3389/fcell.2021.628463
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Rejuvenates Aged Human Mesenchymal Stem Cells by Regulating Autophagy and Improves Cardiac Protection After Infarction

Abstract: The protective effects of mesenchymal stem cell (MSC)-based therapy for myocardial infarction (MI) are largely hampered as they age. Apelin is an endogenous ligand of its receptor APJ and plays an essential role in regulating multiple biological activities including MSC proliferation and survival. In this study, we investigated whether Apelin regulates MSC senescence and whether its overexpression could rejuvenate aged MSCs (AMSCs) to improve cardiac protection following infarction in mice. MSC senescence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that autophagy plays a critical role in the senescence of MSCs and that reducing autophagy diminishes the tolerance of stem cells under various stresses [ 35 , 38 , 49 ]. Pre-activation of autophagy with rapamycin was shown to promote the survival of MSCs in the infarcted myocardium [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that autophagy plays a critical role in the senescence of MSCs and that reducing autophagy diminishes the tolerance of stem cells under various stresses [ 35 , 38 , 49 ]. Pre-activation of autophagy with rapamycin was shown to promote the survival of MSCs in the infarcted myocardium [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reviewed the relations between cellular senescence and autophagy [ 30 , 31 ] and suggested that autophagy plays a dual role in the regulation of MSC senescence. Upregulation of autophagy can decrease the apoptosis of aged MSCs in the condition of myocardial infarction [ 34 , 35 ], restore the biological properties of aged MSCs [ 76 ], rejuvenate MSCs derived from patients with idiopathic pulmonary fibrosis [ 49 ], and reduce the senescence of patellar tendon stem/progenitor cells [ 77 ]. Compared with young MSCs, aged MSCs have significantly reduced autophagic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the engraftment of NDNF-overexpressing old MSCs was shown to improve cardiac function in mice after myocardial infarction [109,110]. Similarly, overexpression of apelin, an endogenous ligand that might be involved in the regulation of MSC senescence, rejuvenated human AT-MSCs by increasing autophagy and promoted cardioprotection following myocardial infarction in mice [111]. Increased expression of macrophage migration inhibitory factor (MIF) also rejuvenated aged human BM-MSCs by activating autophagy and improving their survival under serum deprivation/hypoxia in vitro [112].…”
Section: Therapeutic Implications Of Msc Senescence Targetingmentioning
confidence: 99%
“…In a mouse model of hindlimb ischemia, Apelin treatment increased the viability of adipose-derived MSCs by promoting autophagy during hypoxia via activation of the Akt signaling pathway, leading to a better therapeutic efficacy [ 16 ]. Furthermore, overexpression of Apelin rejuvenated the aged-MSCs and enhanced their cardioprotective effects in MI [ 17 ]. Nonetheless, whether pretreatment of Apelin-13 can enhance the survival of MSCs in the ischemic heart and thereby improve cardiac repair and the underlying mechanisms remains unclear.…”
Section: Introductionmentioning
confidence: 99%